Eisler’s Notes on Hollywood and the Film Music Project, 1935-42 - Bick, Sally M. A. (Current Musicology, 2008)
In 1947, Hanns Eisler in collaboration with Theodor Adorno published a small but important book entitled Composing for the Films. The book represents a significant contribution to film studies, cultural criticism, and discipline of twentieth-century musical practice. It also provides on of the few extended historical texts from the 1940s that deconstructs Hollywood musical practice while probing the wider theoretical implications of motion picture music. Eisler’s writings and The Film Music Project constituent one of the most astute examinations of Hollywood musical practice for its time.